2016
DOI: 10.1155/2016/7412431
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed Oilcake Extract Mediated Green Synthesis of Silver Nanoparticles and Its Antibacterial and Cytotoxic Activity

Abstract: Agroindustrial byproduct mediated green synthesis of silver nanoparticles was carried out using cottonseed oilcake (CSOC) extract. The aqueous silver nitrate formed stable silver nanoparticles with CSOC extract as a reducing agent for Ag+to Ag0. The synthesized nanoparticles were characterized using energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD) techniques. The synthesized silver nanoparticles (AgNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Using different concentrations of nanoparticles, the IC50 value showed different values of (% cell viability) and (% cell inhibition) for the different cells’ lines depending on the time of incubation [ 25 , 26 , 27 ]. There are several biological bases of AgNPs synthesis, and the difference between the current prepared materials compared to the others is the source of the biological route [ 28 , 29 , 30 , 31 , 32 ]. Here, the difference between the current work and previous ones is that we intended to prepare AgNPs via the biological route using Ganoderma enigmaticum as well as Trametes ljubarskyi white rot fungus materials.…”
Section: Introductionmentioning
confidence: 99%
“…Using different concentrations of nanoparticles, the IC50 value showed different values of (% cell viability) and (% cell inhibition) for the different cells’ lines depending on the time of incubation [ 25 , 26 , 27 ]. There are several biological bases of AgNPs synthesis, and the difference between the current prepared materials compared to the others is the source of the biological route [ 28 , 29 , 30 , 31 , 32 ]. Here, the difference between the current work and previous ones is that we intended to prepare AgNPs via the biological route using Ganoderma enigmaticum as well as Trametes ljubarskyi white rot fungus materials.…”
Section: Introductionmentioning
confidence: 99%
“…No similar color changes were seen in the control silver nitrate solution without leaf extract. Such color changes result from the oscillations of free electrons in the reaction mixture of the resultant nanoparticles [33,34].…”
Section: Visual Observationsmentioning
confidence: 99%
“…[24], Solanum indicum L. [25], Acorus calamus [26], Sunroot [27], Indigofera oblongifolia [28], Aloe fleurentiniorum [29], Amorphophallus paeoniifolius [30], Malus domestica [31]. Moreover, other biological sources of AgNps synthesis are also available, such as cow milk [32], Cottonseed Oilcake [33], vegetable waste [34], coconut (Cocos nucifera) oil [35], Spirulina microalgae [36], seaweed Spyridia filamentosa [37]. Such biological sources act rapidly, are non-toxic, cost-effective, pollution-free and therefore eco-friendly [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In order to improve the stability of AgNPs in solution, many inorganic and organic, synthetic and natural, and biotic and abiotic materials were used as capping agents. [8][9][10] In recent years, the researchers have confirmed the therapeutic properties of silver nanoparticles synthesized by several plants such as Spirulina microalgae, [8] Cordia dichotoma, [9] Diospyros Montana, [10] Cassia angustifolia, [11] Cocos nucifera, [12] Panchakavya, [13] Cottonseed oilcake, [14] and mixed vegetables. [15] It has been revealed that silver nanoparticles synthesized using plants have excellent non-cytotoxicity potential against human normal cells (HUVECs), antioxidant property against free radicals such as DPPH, antibacterial effects against Staphylococcus species, Streptococcus species, Bacillus species, Salmonella species, and Pseudomonas species, and antifungal potentials against Candida species.…”
Section: Introductionmentioning
confidence: 99%